The Influence of Internships and Learning Achievement on Work Readiness with Attitude As A Mediating Variable Among 12th Grade Vocational High School Students - Rahmawati, Rosalina; Rosy, Brillian (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: Internship, Learning Achievement, and Good Attitude are very important for every vocational high school student to have. This can affect the readiness of students to enter the world of work that suits their competencies and majors in the future. Purpose: This research aims to determine the effect of internship and learning achievement on work readiness through attitude as a mediating variable in class 12th grade vocational high school students. Novelty: The samples used in this research were 12th grade students of SMK YPI Darussalam 2 Cerme with all majors, namely Office Management, Clinical and Community Pharmacy, Medical Laboratory Technologist, Digital Business, Accounting, Fashion Design and Production, totaling 79 students. The sampling technique used total sampling. Research Methods: This research uses data collection methods through distributing questionnaires. The data analysis technique used is Partial Least Squares (PLS) analysis with SmartPLS software version 4.1.1.2 which consists of measurement model test (outer model), structural model test (inner model), and hypothesis testing. Results: This finding states that both direct and indirect effects of internship and learning achievement on work readiness through attitudes have a significant influence. Research Contributions: This research is expected to be one of the bases for curriculum design and teaching strategies to support the work readiness of competent and highly competitive graduates.